Bioretention Design Simulation for Efficient Urban Stormwater Reduction - Wicaksono, Ega Fajar; Hidayah, Entin; Fildzah, Cantika Almas (Journal of the Civil Engineering Forum, 2025)
The population increases, leading to extensive urbanization and the consequent rise in impervious surfaces. This urbanization trend has exacerbated stormwater runoff issues, necessitating sustainable stormwater management strategies. Low Impact Development (LID) techniques, such as bioretention, have emerged as promising solutions to mitigate the adverse effects of increased impervious surfaces on stormwater management. Through drainage simulation using EPA SWMM 5.2 software, this study assessed the effectiveness of bioretention in mitigating stormwater runoff within Pesona Regency Housing in Jember Regency. In this approach, hydrological techniques use rainfall for a 2-year return period based on the typology of the study area. The bioretention scenarios used coverage of 5%, 10%, and 20% of the subcatchment area as Scenario 1, 2, and 3. The simulation revealed promising reductions in peak runoff discharge across various scenarios, with average reduction rates of 80%, 88%, and 92% for Scenarios 1, 2, and 3, respectively. However, the effectiveness of bioretention varied across different junctions and scenarios due to factors such as location, junction area coverage, soil properties, and local drainage patterns. While larger bioretention areas generally resulted in greater runoff reduction, the study underscores the importance of considering location and cost-effectiveness in bioretention design. Overall, this research provides valuable insights into the efficacy of bioretention as a stormwater management strategy in rapidly urbanizing areas, offering guidance for property developers in planning flood-resistant housing with LID bioretention.